siRNA screen of ES cell-derived motor neurons identifies novel regulators of tetanus toxin and neurotrophin receptor trafficking - Terenzio, Marco; Golding, Matthew; Schiavo, Giampietro (Frontiers in Cellular Neuroscience, 2014)
Neurons rely on the long-range transport of several signalling molecules such as neurotrophins and their receptors, which are required for neuronal development, function and survival. However, the nature of the machinery controlling the trafficking of signalling endosomes containing activated neurotrophin receptors has not yet been completely elucidated. We aimed to identify new players involved in the dynamics of neurotrophin signalling endosomes using a high-throughput unbiased siRNA screening approach to quantify the intracellular accumulation of two fluorescently tagged reporters: the binding fragment of tetanus neurotoxin (HCT), and an antibody directed against the neurotrophin receptor p75NTR. This screen performed in motor neurons differentiated from mouse embryonic stem (ES) cells identified a number of candidate genes encoding molecular motors and motor adaptor proteins involved in regulating the intracellular trafficking of these probes. Bicaudal D homolog 1 (BICD1), a molecular motor adaptor with pleiotropic roles in intracellular trafficking, was selected for further analyses, which revealed that BICD1 regulates the intracellular trafficking of HCT and neurotrophin receptors and likely plays an important role in nervous system development and function.